Digital image watermarking using genetic algorithm in DWT and SVD transform - Sridevi, T; Fatima, S.S (Proceedings of third International Conference on Computational Intelligence and Information Technology, 2013)
Digital image watermarking is a technology that it is used to hide the information in an image for copy right protection. The main issues in watermarking are robustness and fidelity. In this paper, Discrete Wavelet Transform (DWT) is applied and Singular Value Decomposition (SVD) is also used. Genetic algorithm is implemented for embedding the watermark to achieve robustness and fidelity. It is an optimization technique used to find the positions for embedding the watermark. Attacks are also applied on the watermarked image. Measurements like PSNR and NC are also calculated for watermarked and extracted watermark image.